Effect of IMT-03, an Herbal Formulation in Cyclophosphamide-induced Immunosuppression in Mice (Journal of Basic and Applied Research in Biomedicine, 2022)
Immumomodulatory actions of natural ingredients have been recognized from the time of early civilization. Though herbal medicines are equally used to treat deadly diseases, but till date there are lacks of evidences. In the present work, an herbal preparation IMT-03 was used to find out its immunostimulatory efficacy against chemotherapeutics. Although, most of the individual ingredients present in IMT-03 have been reported for their protective roles against chemotherapeutics, but there is no report in combination. Cyclophosphamide (300 mg/kg, intraperitoneally) induces immunosuppression through myelosuppression. Pretreatment with of IMT-03 at dose of 100 mg/kg and 200 mg/kg in Cyclophosphamide induced immunosuppressive mice showed dose dependently and significantly (p